Taraxacum (sect. Crocea) Christiansen 1942 - Štěpánek, Jan; Kirschner, Jan (Zenodo, 2022)
B. Taraxacum sect. Crocea Christiansen (1942: 255) ≡ Taraxacum subsect. Crocea (M. P. Christ.) Richards (1972: 38) Type :— Taraxacum croceum Dahlstedt (1901: 12) Type :— Sweden [Hälsingland], Vänsjö, Vänsjöhammaren, 12. Jul 1898 M. Östman (S 05-7995!, lectotype, designated by Lundevall & Øllgaard 1999: 74) = Taraxacum sect. Fontana van Soest (1959: 103) ≡ Taraxacum subsect. Fontana (van Soest) Doll (1982: 538) Type :— Taraxacum fontanum Handel-Mazzetti (1907: 100) Type:— Austria, an feuchten Stellen zwischen Steinen in der Rinne ober dem Kaserl im Sendersthal bei Innsbruck gegen das Pleisenjoch, ca. 1800 m, 23 Jul 1903, H. Handel-Mazzetti (WU, no. det. 8943, lectotype, designated by Kirschner & Štěpánek 1997: 92). Introduction The Arctic-Alpidic group characterized by a large disjunction between the northernmost Europe and the Alps, was first recorded from the Balkans by Handel-Mazzetti (1907, as T. fontanum ), then by Hayek (1931, as T. officinale var. fontanum , and finally by Doll (1978). A detailed comparison of the northern species of T. sect. Crocea revealed their sectional identity with the Alpine species referred to as T. sect. Fontana . The first formal synonymization of these two sectional names is published in the present paper, in accordance with the opinion of other experts in Taraxacum (C. I. Sahlin, pers. comm. 1984; I. Uhlemann, a paper in prep.). There are more than 120 northern species and up to 20 distributed in south-central and southern Europe; it should be added that T. sect. Crocea is known to occur in Greenland, Alaska and Canada. With a single, notable exception, all the species are agamospermous. In Bulgaria, there are four agamosperms, and the single sexual diploid species, T. paludosiforme Doll. The most conspicuous features of T. sect. Crocea are leaves with a low number of short and broad lateral segments, broadly winged petioles of outer leaves, outer phyllaries usually appressed to loosely appressed, sometimes their distal part arcuate recurved to arcuate-patent, deep ...